Adolescents Facing Risks in the Use of ICT - Jhon Richard Orosco Fabián; Rocío Pomasunco Huaytalla (Universidad Autónoma de Baja California, 2020)
Information and Communication Technologies (ICT) have impacted adolescents from all sectors of society, and using it without guidance leads directly or indirectly to be exposed to risks. This study evaluates the frequency of risks in the use of ICT in adolescents of the Junín region. The sample consisted of 955 adolescents between the ages of 13 and 19 (M = 15.21, SD = 1.07) from different provinces of the Junín region (Peru). The selection of participants was based on stratified random sampling. Information was collected through an instrument built ad hoc. The results show that there is a significant difference in the knowledge of risks, being higher in women. The main risks to which are exposed are: access to inappropriate content (46.2%), sexting (24.9%), cyberbullying (20.9%), grooming (20.8%), sexcasting (14.8%), sextorssion (12.3%). The differences were significant among the male population in most of the ICT risks that were analyzed. It is concluded that adolescents in the Junín region are exposed to various risks and, therefore, the responsible use of ICT must be oriented.